The study of mosque architecture in Sarawak under the leadership of Pehin Sri Abdul Taib Mahmud / Dato Professor Dr Jamil Hamali ... [et al.] - Hamali, Jamil; Wan Hassan, Sharifah Zakiah; Jimel, Clement; Karim, Abdul Khalid; Mohd Muslim Tan, Ellyana; Muhammad Azmi, Safrina (2012)
Sarawak has a land area of 124,450 square kilometres, roughly the size of Peninsular Malaysia. There are about 700,000 Muslims out of a population of 2,500,000 people (Population Census 2010). The first mosque in Sarawak was a wooden hut built on stilt on the bank of Sarawak River built before 1839. Kuching was then a small town of less than 800 inhabitants, most of them Malays (Sanib Said, 1998). Before Independence, mosques in Sarawak were generally small and they were built with simple material of wood and nipah palm leaves from the limited fund collected from the community and well wishers. After Independence, government machineries and developments attracted all communities, including the Malays and Melanaus who are Muslims to move to towns as workers in the public and private sectors. The old divisional mosques and district mosques were simply too small for Friday prayers. From 1963 to 1983, divisional mosques were rebuilt first in Kuching (1968), followed by Limbang (1972), Sri Aman (1980), Sibu (1980), Sarikei (1983), and Miri (1983). Their rooftops were all designed with domes, and minarets were erected either on the building edges or as stand-alone structures. In the last 30 years (1983-2012), mosque buildings in Sarawak have gone through rapid development and uplift. Almost one or two new mosques of budget around RM1 million were built each year, accredited to the fast pace of economic development and good governance of Muslim affairs under the leadership of the Chief Minister Pehin Sri Haji Abdul Taib Mahmud. The same period witnessed more than half of the mosques were constructed with pyramidal tiered roofs, departing from the dome and minaret period (1963- 1983) and reverting to the style of the 1852 Masjid Besar Kuching and its predecessor. After Independence but more prominently in the last 30 years, Sarawak skyline was introduced to unique concepts and styles in mosque buildings, demonstrating improved economic status and the advancement in building technology and engineering. Behind the building of mosques, apart from their physical outlook, architecture and styles, there are historical